PENINGKATAN KOMPETENSI GURU SEKOLAH MENENGAH KEJURUAN MELALUI PELATIHAN SOFTWARE ENGINEERING - Fivia Eliza; Hastuti Hastuti; Dwiprima Elvanny Myori; Doni Tri Putra Yanto (JTEV (Jurnal Teknik Elektro dan Vokasional), 2019)
Increasing teacher competency is a process that cannot be done instantly. Teachers must always be provided with new knowledge that can be applied to their own needs and institutions. Computer-based learning will greatly help educators in the current era of Information and Communication Technology, especially vocational teachers who teach in productive fields (engineering subjects). The problem faced is the inability of teachers to use computers as learning media. Teachers only use computers to present powerpoint media, even in practical subjects. The teacher has not been able to utilize software engineering that will assist in the practical learning process, such as AutoCAD software in learning Drawing Engineering and PLC software in learning control systems. Therefore, it is necessary to conduct integrated and comprehensive training for teachers in utilizing computers as learning media especially in the use of software engineering. All Muhammadiyah 1 Padang Vocational Middle School teachers and SMK Dhuafa Nusantara Padang were invited to take part in engineering training. In the implementation of the activity there were 15 teacher participants. The training material consisted of the introduction and use of AutoCAD software, and PLC software. The results of this training show that more than 90% of participants have been able to use AutoCAD and PLC software. Besides that, there was an increase in motivation and enthusiasm from the teacher to show performance, both in the use of software for classroom learning and in daily life as a professional who always tried to improve his competence.